Development of Mathematical Achievement, Mathematical Problem-Solving, and Work Commitment by Engaging in Learning Activities Using the CIPPA Model and TGT for Grade 8, Students - Phochat, Juthamat; Panarach, Yupadee (Journal of Computer and Creative Technology, 2025)
This research aimed to 1) compare mathematical achievement before and after learning activities, 2) compare the mathematical achievement after learning activities with the 70% criterion, 3) study the mathematical problem-solving after learning activities, and 4) study the work commitment after learning activities. The sample consisted of Grade 8 students. Research instruments included lesson plans, mathematical achievement test, mathematical problem-solving test, and the questionnaire about work commitment. Data were analyzed by frequency, percentage, mean, standard deviation, and the t-test. The results found that: 1) Students had mathematical achievement after higher than before learning activities was significantly at the .05 level. 2) Students had mathematical achievement after learning higher than the 70% criterion was significantly at the .05 level. 3) Students had mathematical problem-solving skills after learning activities were at a very high level, followed by a good level, and a fair level, respectively. 4) Students had work commitment after learning activities was, overall, at the highest level.